2017
DOI: 10.1111/weng.12284
|View full text |Cite
|
Sign up to set email alerts
|

The use of English in the professional world in China

Abstract: The status and use of English in mainland China are topics of intense interest for researchers, although most previous research has been conducted within the field of education, with few data from the professional world. The current study attempts to focus on the professionals in China and their use of English. The study has drawn data with a questionnaire from 2,247 participants in workplaces across China and 44 of them have been interviewed. The participants are from three types of organization: government, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition, the findings also indicated there was an increasing use of English among Chinese business professionals. This finding is corroborated by a study by He [4] which drew data from 2,247 participants in workplaces from the government, public service unit, and companies across China on their use of English at the workplace. Despite infrequent use of English among Chinese professionals, the results indicated that the majority of the respondents did recognise the high importance of English in the workplace.…”
Section: Introductionmentioning
confidence: 52%
“…In addition, the findings also indicated there was an increasing use of English among Chinese business professionals. This finding is corroborated by a study by He [4] which drew data from 2,247 participants in workplaces from the government, public service unit, and companies across China on their use of English at the workplace. Despite infrequent use of English among Chinese professionals, the results indicated that the majority of the respondents did recognise the high importance of English in the workplace.…”
Section: Introductionmentioning
confidence: 52%
“…One consequence of the emergence of English as the world's de facto global language is that, whatever a person's first-language background, he or she will be disadvantaged without learning at least some English. The variety of English which has the greatest currency is Standard English (He, 2017a(He, , 2017bLi, 2007). Despite being standardized and codified for decades (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, students are tired of their “test-driven English” and “dumb English” ( yăbā yīngyŭ ; Guo and Yin, 2014; He, 2018, 2020; He and Li, 2009). Both popular sayings reflect a widely perceived learning outcome whereby passing multifarious English examinations with flying colors proves much easier compared with expressing oneself fluently and spontaneously with confidence (Zheng, 2010).…”
Section: Critical Issues In Elt In Chinamentioning
confidence: 99%